Digital Da'wah Strategies in The Era of Social Media and Digital Platforms: Opportunities, Challenges, and Effective Practices - Abrori; Awaluddin Pimay; Nasihun Amin (Yayasan Darussalam Bengkulu, 2026)
In the digital era, social media has become a tool with many advantages in supporting da'wah activities. These include the ability to reach a wide audience, direct interaction, and the speed of message dissemination. However, there are also obstacles to overcome, such as the rapid flow of content uploaded at any given time, the potential for the spread of false or misleading information, and differences in perception and interpretation of da'wah messages among diverse da'wah partners. Many cases arise from the communication style of some preachers on social media, which can sometimes be rude, offensive, or display excessive lifestyles. The main focus of this article is to formulate da'wah strategies that are appropriate to the dynamics of the digital era. The findings indicate that contemporary da'wah strategies utilize various digital tools such as social media, podcasts, YouTube, blogs, da'wah apps, and cross-platform strategies. The process involves a series of structured steps including audience analysis, platform selection, content production, message distribution, and regular evaluation to ensure message delivery remains relevant, broad, and sustainable. The implementation of da'wah needs to use a creative and interactive approach so that it can reach a wider target to all audiences, especially the millennial generation Z group. Short visual-based content, supported by technology, has proven effective in attracting attention and strengthening religious messages.